THE IMPACT OF SERVICE QUALITY ON CUSTOMER SATISFACTION TOWARDS STAR HOTELS IN TAMILNADU - S.SEKAR; Dr.B.SUDHA (The journal of contemporary issues in business and government, 2021)
The interaction among customers’ satisfaction is the level of product. It is a deep required to stay a member of a particular hospitality sector and we retain (as well as) exert elevated amounts of effort in account of a Resin hotel. It is also defined as an underlying mental connection to the hospitality sector. The study is primarily focused on customer loyalty and the quality of products or services of quality dimension. For the service industry, quality of service is a big problem. The aim of the work is to discover out the variables which differ between the participants’ demographic factors and independent factors. The doctors collected the variable, selected on both secondary sources. By focusing on front office workers only this study identifies variables of service quality and analyzed the expectations and awareness levels of such services of a customer. The effects of this quantitative assessment of the quality of service can provide some insights on how consumers rate the quality of service and evaluate the satisfaction of customers. The research implies that service efficiency plays a significant role as a catalyst for increased customer satisfaction of hotel service. Supervisors should concentrate on compassion, flexibility, responsiveness and reliability to achieve a customer satisfaction that contributes to customer satisfaction and business benefit.